2014
DOI: 10.1208/s12249-014-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein/Polysaccharide-Stabilized Emulsions: Effect of Polymer Type and pH on Release and Topical Delivery of Salicylic Acid

Abstract: Abstract. Emulsions are widely used as topical formulations in the pharmaceutical and cosmetic industries. They are thermodynamically unstable and require emulsifiers for stabilization. Studies have indicated that emulsifiers could affect topical delivery of actives, and this study was therefore designed to investigate the effects of different polymers, applied as emulsifiers, as well as the effects of pH on the release and topical delivery of the active. O/w emulsions were prepared by the layer-by-layer techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The transdermal delivery results of salicylic acid from the redispersed oil powders were also similar to that obtained by Combrinck et al (14). With regards to the effect of pH, the degree of ionization of salicylic acid could have affected the transdermal delivery thereof, with a decrease in permeation with increasing ionization of salicylic acid, according to the pH partition hypothesis.…”
Section: In Vitro Skin Absorptionsupporting
confidence: 86%
See 1 more Smart Citation
“…The transdermal delivery results of salicylic acid from the redispersed oil powders were also similar to that obtained by Combrinck et al (14). With regards to the effect of pH, the degree of ionization of salicylic acid could have affected the transdermal delivery thereof, with a decrease in permeation with increasing ionization of salicylic acid, according to the pH partition hypothesis.…”
Section: In Vitro Skin Absorptionsupporting
confidence: 86%
“…The release data obtained for the template emulsions and redispersed powders were similar to that obtained by Combrinck et al (14). It was therefore concluded that electrostatical interactions between the salicylic acid and the emulsifiers of the emulsion droplets had affected the release of salicylic acid from these formulations.…”
Section: Release Of Active Ingredient From Formulationssupporting
confidence: 84%
“…[31] Other similar nonionic surfactants were also employed: Tween 20, 40, 60, and 80 (polyoxyethylene sorbitan monolaurate), [66][67][68] Span 20, 40, 60, and 80 (sorbitan monolaurate) [69,70] and Kolliphor HS-15 (polyoxyethylene-660-hydroxystearate) (see examples in Figure 1B). [71] In addition, common surfactants of different chemical nature can be also used for NEs preparation: poloxamers (also known as Pluronics), [72] amphiphilic proteins like casein, [73,74] lactoglobulin, [75] polysaccharides (e.g., gums, starch derivatives), [76] and PEG containing block copolymers. [77] Ionic surfactants have also been used for preparation of NEs, like for instance, sodium dodecyl sulfate and docusate sodium salt (AOT).…”
Section: Surfactantmentioning
confidence: 99%
“…Protein concentration, pH, temperature and ionic strength had an effect on the emulsification activity of the proteins (Combrinck et al ., 2014). In addition, glycation of proteins is also known to affect their emulsification activity, and in this study, emulsification properties are also determined (Table 5).…”
Section: Resultsmentioning
confidence: 99%